Desenvolvimento de um fotômetro portátil usando LED como fotodetector e de procedimentos analíticos automáticos empregando multicomutação em fluxo - Silva, Milton Batista da (2008)
This work involves the development of portable photometer using a LED (Light Emitting Diode) as source of electromagnetic radiation and another one LED as photodetector. The viability of this proposal was demonstrated in an automatic photometric titration procedure, which was implemented based on the binary search process. The sensitivity improvement of the classic analytical methods to improve limit of detention is a current demand of the analytical chemistry, to attain the maximum limits established by the regulatory agencies. In photometric detention a resource to attain this requirement would be the increasing of the optical path of the flow cell. In flow analysis, the geometry of the usual cells flow does not allow the increase of the pathlength. The availability in the market of LED with emission beam high intensity within narrow angle of scattering, allows its use to develop homemade photometer. In this work, a LED with this characteristic was used to allowed the use a flow cell with optical path of 200 mm. The flow cell was designed with geometry appropriate to allow the direct coupling of radiation source (LED) and photodetector. According to CONAMA (National Advice of the Environment), orthophosphate is the chemical species that the maximum concentration allowed in fresh water is in the order of g L-1 level. The use of flow cell with optical path of 200 mm was evaluated in an automatic procedure for determination of orthophosphate in waters. The procedure was implemented using the multicommutation flow injection analysis process, using the photometric method based on the reaction with ammonium molybdate and reduction with stannous chloride. Different photodetectors have been employed in prototypes of photometers, thus aiming to compare the performance of the usually employed photodetectors, a set of experiments was carried out, submitting the photodetectors to the same work conditions. The photometric determination of orthophosphate in waters was selected as model to test the response of the used photodetectors.